PERKEMBANGAN EFISIENSI PENGGUNAAN MODAL KERJA DALAM MENGHASILKAN LABA PADA TARAWANGSA WOOD INSTRUMENT PERIODE 2010-2014 - Dahlia Dahlia (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2015)
Financial or we can say working financial every company need working financial operations every day in order to fast, because of that company need to use the Working Capital Efficiency in order to be able to produce the optimal profit. So that the formulation of the problem in this research is how the developments in the Working Capital Usage Efficiency Produces Profit In Tarawangsa Wood Instrument period 2010-2014. This research has the objective to determine developments in the Working Capital Efficiency Using Generate Profit On Wood Tarawangsa Wood Instruments. Current research variable Ratio, Return On Investment (ROI), Turnover Cash, Accounts Receivable Turnover, turnover Inventory From the analysis above use of working capital from 2010-2014 tends to rise (more efficient ) but is relatively slow , with the rate that is small efficiently too. Keywords: Rentability, IEMK, Liquidity, Cash Turnover, Inventory Ratio, Cccounts Receivable Turnover